Comparison of ultrasound biomicroscopy and spectral-domain anterior segment optical coherence tomography in evaluation of anterior segment after laser peripheral iridotomy - Xiao-Yun Ma; Dan Zhu; Jun Zou; Wen-Jie Zhang; Yi-Lin Cao (International Journal of Ophthalmology, 2016)
AIM: To quantitatively assess narrow anterior chamber angle using spectral-domain anterior segment optical coherence tomography (SD-AS-OCT) and ultrasound biomicroscopy (UBM), and to evaluate the correlations and consistency between SD-AS-OCT and UBM. METHODS: Fifty-five eyes from 40 patients were examined. Patients were diagnosed with primary angle-closure glaucoma (PACG) remission (11 eyes from 8 patients), primary angle closure (PAC, 20 eyes from 20 patients) and PAC suspect (24 eyes from 12 patients). Each eye was examined by SD-AS-OCT and UBM after laser peripheral iridotomy (LPI). The measurements of SD-AS-OCT were angle open distance (AOD), anterior chamber angle (ACA), trabecular iris angle (TIA), and trabecular iris space area (TISA). UBM measurements were AOD and TIA. Correlations of AOD500 and TIA500 between UBM and AS-OCT were assessed. All parameters were analysed by SPSS 16.0 and MedCalc. RESULTS: ACA, TIA and AOD measured by SD-AS-OCT reached a maximum at the temporal quadrant and minimum at the nasal quadrant. TISA reached the maximum at the inferior and minimum at the superior quadrant. Group parameters of AOD500 and AOD750 showed a linear positive correlation, and AOD750 had less variability. UBM outcomes of AOD500 and TIA500 were significantly smaller than those of SD-AS-OCT. The results of the two techniques were correlated at the superior, nasal and inferior quadrants. CONCLUSION: Both UBM and SD-AS-OCT are efficient tools for follow-up during the course of PACG. We recommended using parameters at 750 µm anterior to the sclera spur for the screening and follow-up of PACG and PAC. The two methods might be alternatives to each other.